Relationships between heavy metal concentrations in three different body fluids and male reproductive parameters: a pilot study - Ten Jorge; López-Espín José J; Moreno-Grau Stella; Elvira-Rendueles Belén; García-Sánchez Antonio; Martínez-García María J; Vergara-Juárez Nuria; Roca Manuela; Moreno José M; Mendiola Jaime; Bernabeu Rafael; Torres-Cantero Alberto M (BMC, 2011)
Abstract Background Animal studies have shown the reproductive toxicity of a number of heavy metals. Very few human observational studies have analyzed the relationship between male reproductive function and heavy metal concentrations in diverse biological fluids. Methods The current study assessed the associations between seminal and hormonal parameters and the concentration of the 3 most frequent heavy metal toxicants (lead, cadmium and mercury) in three different body fluids. Sixty one men attending infertility clinics that participated in a case-control study to explore the role of environmental toxins and lifestyles on male infertility were analyzed. Concentration of lead, cadmium and mercury were measured in blood and seminal plasma and whole blood using anodic stripping voltammetry and atomic absorption spectrophotometry. Serum samples were analyzed for follicle-stimulating hormone, luteinizing hormone and testosterone. Semen analyses were performed according to World Health Organization criteria. Mann-Whitney test and Spearman's rank correlations were used for unadjusted analyses. Multiple linear regression models were performed controlling for age, body mass index and number of cigarettes per day. Results There were no significant differences between cases and controls in the concentrations of heavy metals in any of the three body fluids. In multivariate analyses using all subjects no significant associations were found between serum hormone levels and metal concentrations. However there was a significant positive association between the percentage of immotile sperms and seminal plasma levels of lead and cadmium. Conclusions Our results suggest that the presence of lead and cadmium in the reproductive tract of men may be related to a moderate alteration of their seminal parameters.